Pilot study to evaluate a tailored text message intervention for pregnant smokers (MiQuit): study protocol for a randomised controlled trial - Cooper, Sue; Foster, Katharine; Naughton, Felix; Leonardi-Bee, Jo; Sutton, Stephen; Ussher, Michael; Leighton, Matthew; Montgomery, Alan; Parrott, Steve; Coleman, Tim (BioMed Central, 2015)
Background